Identity of Lagochilus xianjiangensis (Lamiaceae), a doubtful species from the Tianshan Mountains of China - Chen, Yan-Yi; Wang, Yan; Wu, Xue-Xue; Wang, Qiang (Phytotaxa, 2025)
Lagochilus lanatonodus and L. xianjiangensis are perennial herbs endemic to China. Based on our critical examination of specimens and field investigations, the characters used to distinguish the two species are unstable. In the present study, molecular phylogenetic analyses based on the Angiosperms353 gene set are conducted, and the results fully support that L. xianjiangensis is nested within L. lanatonodus. Combining the results of morphological and molecular phylogenetic analyses, we here reduced L. xianjiangensis to a synonym of L. lanatonodus.